A new method to analyse gas flowrate of goaf vertical wells with mining activities on extra-thick coalbeds. (10th February 2021) - Xiong, Wei; Chen, Yong; Tan, Cheng; Zhou, Hou-Quan; Liu, Yan-Bao
The goaf vertical well is a widely used technology applied to address the gas transfinite issues. Gas production characteristics of goaf vertical wells in extra-thick coalbeds are significantly different from those in traditional coalbed. In this paper, a permeability model versus volumetric strain in coal and surround stratum was established based on which the above stratum was divided into four zones with the spatial scale expressions of permeability was established in each zone. Furthermore, a model calculating gas rate in goaf vertical wells was established. To verify the model, the field data of the well #2 in Weijiadi Coal Mine were compared with theoretical values with good fitness. Also the gas rate was discussed at different locations with different relationships between permeability and gas extraction radius. This paper can be used to estimate the gas rate, location and extraction pattern design from of goaf vertical well. [Received: 30 June 2019; Accepted: 13 December 2019]